The condition of the intellectual potential and platform chemicals base for the production of engineering polymers in Poland. Shell we be able to keep up with the main global players? - Kijeński, J.; Kijeńska, M.; Rejewski, P. (Polimery, 2021)
In the opinion of experts, engineering polymers and agrochemicals are the only fields, in which the European chemical industry can successfully compete in the global market. Polish companies which are grouped in the Great Chemical Synthesis sector have not shown any high gain development down-stream for years. An analysis of the potentials for growth in the field of engineering chemicals in Poland, taking into consideration global trends, the competence and tradition of Polish companies and their R&D base as well as the shortcomings of the production sector of platform chemicals have been presented.